(untitled) (Oxford [England], 1995)
This book presents aquaculture sector planning. The first chapter provides an over view of the sector. Chapter 2 by summarizing the many environmental, social and market factor which influence the sector's growth,...
Quy hoạch và phát triển nghề cá,Quy hoạch và quản lý nuôi trồng thủy sản
Keywords: Aquaculture industry,Aquaculture industry; Management,Government policy